(untitled) (Medical Forum Monthly, 2023)
Objective: The basic aim of the study is to find the new biomarkers for the early detection of Alzheimer's disease. Study Design: Prospective observational study Place and Duration of Study: This study was conducted at the Ayub Teaching Hospital Abbottabad and Women Medical College Abbottabad, covering the period from February 2023 to July 2023. Methods: A total of 120 participants were enrolled, with two distinct groups formed: a control group of cognitively healthy individuals (n=60) and a group diagnosed with mild cognitive impairment (MCI) or early-stage AD (n=60). Results: A total of 120 participants were enrolled in the study, with an even distribution between the control group (n=60) and the mild cognitive impairment (MCI) or early-stage Alzheimer's disease (AD) group (n=60). The participants' age ranged from 50 to 85 years, reflecting the target age range. Serum and plasma samples from both groups were subjected to biomarker analysis. Notably, levels of amyloid-beta were found to be significantly elevated in the MCI/AD group compared to the control group. Similarly, tau protein levels exhibited a marked increase in the MCI/AD group, aligning with neurodegenerative processes. Conclusion It is concluded that this study contributes valuable evidence to the realm of early AD detection by demonstrating the potential of amyloid-beta and tau protein as blood-based biomarkers. The integration of cognitive assessments, biomarker analysis, and neuroimaging enhances the credibility of the findings.